Analysis of HACCP implementation in the Malaysian halal Industry / Muhammad Raziq Ramzi and Azri Bhari - Ramzi, Muhammad Raziq; Bhari, Azri (Academy of Contemporary Islamic Studies (ACIS), 2021)
Nowadays in Malaysia, cases of foodborne disease in many regions with the objective of bringing HACCP to communities, particularly tiny, free-lance food companies who are not normally radar-related. Halal food is an important component. As the Muslim world's population grows, so does the demand for food. Although the concept of halal overlaps with food safety and quality, the infrastructure for both food safety and the certification scheme are separate. The objective of the research is to analyze the HACCP implementation in the Malaysian industry. This research has chosen this nation based on following factors. Food safety and Halal are synonymous in Muslim countries. This is because Halal requires safe, healthy (toyyiban), and sanitary features. Then, Meat preparation and processing is one of the most important parts of Halal for Muslims and on the other hand, several impediments remain, including a lack of experience, a lack of resources, cumbersome processes, operational unpredictability, and so on. The most serious worry is a lack of experience and capacity to execute HACCP, as well as a lack of employee commitment to food safety. This study was conducted using qualitative research, using library and observation method to collect data. Then the data were analyzed using inductive, deductive and comparative methods of the topic material being discussed. The finding showed that Malaysia has established technical committee food system and agencies or bodies to maintain the HACCP implementation. However, there are problem occur especially about the cases of foodborne illness which is often happen with free-lance food operator and small operator but rarely happens with mass or big production company. Researchers hope that this research will help to give boost and insight towards what is really happen with Malaysia’s Halal food with their HACCP implementation and shows what part that still to focused on regarding the cases and challenges that faces when implementing the HACCP in Malaysia. To emphasize, what we hope that the government will find solution for the small operator and free-lance food operator to produce more safe food and quality assurance.